The Android malware handbook manual analysis and ML-based detection - Han, Qian; Tetali, Sai Deep; Mandujano, Salvador; Porst, Sebastian; Subrahmanian, V. S.; Xiong, Yanhai (No Starch Press, 2024)
"Explores the history of Android attacks and covers static and dynamic approaches to analyzing real malware specimens, machine-learning techniques to detect malicious apps, and how to identify banking trojans, ransomware, and SMS fraud"--
Includes index. - Description based on print version record and CIP data provided by publisher; resource not viewed
Keywords: Android (Electronic resource); Malware (Computer software); Operating systems (Computers) -- Security measures; Mobile computing -- Security measures; Machine learning; Logiciels malveillants; Systèmes d'exploitation (Ordinateurs); Sécurité; Mesures; Informatique mobile; Sécurité; Mesures; Apprentissage automatique